Taxonomic revision of the Neotropical genus Argentinomyia Lynch-Arribálzaga, 1891 (Diptera: Syrphidae), with description of 16 new species - Montoya, Augusto L.; Wolff, Marta (Zootaxa, 2023)
The Neotropical flower fly genus Argentinomyia Lynch-Arribálzaga (Diptera: Syrphidae) is revised and rediagnosed. An updated key to the Neotropical genera of Bacchini and Melanostomini is provided. As a result of the ongoing systematic study of the genus, sixteen new species were discovered and described: Argentinomyia aurifacies Montoya & Thompson sp. nov. (Dominican Republic), Argentinomyia belmira Montoya & Wolff sp. nov. (Colombia), Argentinomyia humboldti Montoya & Wolff sp. nov. (Colombia and Ecuador), Argentinomyia ivani Montoya sp. nov. (Colombia), Argentinomyia jalcaensis Thompson & Montoya sp. nov. (Perú), Argentinomyia jamaicensis Montoya sp. nov. (Jamaica), Argentinomyia norrbomi Montoya sp. nov. (Brazil), Argentinomyia occidentalis Montoya & Wolff sp. nov. (Colombia), Argentinomyia plaumanni Thompson & Montoya sp. nov. (Brazil), Argentinomyia sagoti Montoya sp. nov. (Mexico), Argentinomyia serendipia Montoya sp. nov. (Colombia), Argentinomyia spinifemorata Montoya sp. nov. (Colombia), Argentinomyia taina Montoya & Thompson sp. nov. (Dominican Republic), Argentinomyia teresae Montoya sp. nov. (Colombia), Argentinomyia transversalis Montoya sp. nov. (Colombia and Bolivia) and Argentinomyia tropandeana Montoya sp. nov. (Colombia, Ecuador and Perú). Five new synonyms are proposed for four species: Melanostoma melanocerum (Williston, 1891) = Argentinomyia catabomba (Williston, 1891), Braziliana columbiana (Enderlein, 1935) = Argentinomyia fastigata (Fluke, 1945), Braziliana peruviana (Shannon, 1927), Braziliana thiemei (Enderlein, 1935) = Argentinomyia longicornis (Walker, 1836) and Rhysops funerea (Hull, 1949) = Argentinomyia nigrans (Fluke, 1945). Lectotypes are designated for the following names: Melanostoma catabombum Williston, 1891, Melanostoma crenulatum Williston, 1891, Melanostoma longicornis Williston, 1888, Melanostoma melanocerum Williston, 1891 and Pipiza longicornis Walker, 1836. Twenty-six species are redescribed and an updated key proposed for 41 out of the 47 species recognized as valid. Synonyms, descriptions, comparative diagnosis, high-definition color photographs of overall appearance, illustrations of the male genitalia as well as field photographs are provided. The known distribution ranges are mapped and the biogeographical affinity and endemism are discussed. Female genitalia are described for the first time for the genus. Argentinomyia berthae (Lima, 1946) is rediscovered and redescribed, including the designation of a neotype. The taxonomic status of Argentinomyia scitula (Williston, 1888) is considered doubtful and needs further study. Taxonomic notes are provided for Argentinomyia aenea (Willistoni, 1891) and A. huitepecensis Montoya, 2020. The high diversity, the biogeographical affinities, the noteworthy endemism patterns, new country records as well as the morphological variation evidenced in the present revision suggest that the genus is much more diverse than it appears, with many new species that undoubtedly remain to be described from unexplored areas of the Neotropics. Our study provides a thorough morphological assessment as well as the updated biogeographical distribution, which constitute a starting point to answer questions and propose hypotheses about the phylogenetic relationships, historical biogeography, diversification patterns and conservation of Argentinomyia in forthcoming contributions.